2000
DOI: 10.3109/01677060009083474
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions Between GTP Cyclohydrolase I and Tyrosine Hydroxylase inDrosophila

Abstract: Tyrosine hydroxylase requires the regulatory cofactor, tetrahydrobiopterin, for catecholamine biosynthesis. Because guanosine triphosphate cyclohydrolase I is the rate limiting enzyme for the synthesis of this cofactor, it has a key role in catecholamine production. We show that GTP cyclohydrolase and tyrosine hydroxylase (TH) are co-localized in the Drosophila central nervous system. Mutations in the Punch locus, which encodes GTP cyclohydrolase, reduce TH activity; addition of cofactor to crude extracts coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…This cofactor is required for the conversion of tyrosine to dopamine (37), which has at least two possible roles in immunity. First, dopamine is one of two main Drosophila catecholamines, which are important for the stress response in both insects and mammals (38).…”
Section: Discussionmentioning
confidence: 99%
“…This cofactor is required for the conversion of tyrosine to dopamine (37), which has at least two possible roles in immunity. First, dopamine is one of two main Drosophila catecholamines, which are important for the stress response in both insects and mammals (38).…”
Section: Discussionmentioning
confidence: 99%
“…As in mammals, these studies have demonstrated that GTPCH and TH co-localize within Drosophila neurons and that the activity of TH is precisely correlated with the in vivo activity of GTPCH (22), whereas coimmunoprecipitation studies suggest that GTPCH and TH from head extracts physically associate (22). Interestingly, it has been observed that homozygous Punch mutants exhibit phenotypes similar to those of pale homozygotes (23,24), whereas biochemical analyses of heterozygous Punch mutant flies reveal a reduction in the in vivo activity of TH due to reduced levels of the cofactor, BH 4 (22). Surprisingly, the introduction of exogenous BH 4 fails to restore full TH activity in extracts of the heads of Punch mutants despite the fact that TH protein levels are unaffected by Punch mutations.…”
mentioning
confidence: 99%
“…We reasoned that because GTPCH is rate limiting for the synthesis of BH 4 in Drosophila (Krishnakumar et al, 2000) and the cofactor, in turn, is limiting for DA synthesis, overexpression should elevate both cofactor and DA levels. The pharmacological analyses described above led to the prediction that DA overexpression should lead to greater resistance to the effects of paraquat if its effects were initially limited to dopaminergic cells.…”
Section: Paraquat Causes Selective Loss Of Da Neuron Clustersmentioning
confidence: 99%